The demographics of computer-mediated communication: A review of social media demographic trends among social networking site giants - Gambo, Sarah; Ozad, Bahire Ofe (Elsevier, 2020)
The emergence of social network sites (SNSs) and their extraordinary expansion across the globe has articulated the crucial role computer-mediated communication now plays in human interactions. Though everyone seems caught-up in this new communication frenzy, the appears to be a significant dissimilarity and gaps in the demographics of SNS usage. The aforementioned subject has been the focus of much scholarly attention in recent years as scholars and researchers sought to understand and explain the issue. Most literature on this topic have been focused on the following preoccupations: How is SNSs usage distributed amongst various demographic groups, gender and SNS usage, and SNS and age factor. These issues constitute the focus of this review article. This paper undertakes a review of published research studies on demographic issues on social network sites. Three major findings surfaced from the inductive analysis of the study results: the demographic distribution of SNS usage presents a clear domination of youths and women; men and women have different motivation in their SNS usage with women pursuing specific targets and men being more general; and older people are more concerned with privacy in their social media usage than youths.
Keywords: Computer -mediated communication; Social media; Demographics; Social network sites; Online platforms; SNS usage